2013
DOI: 10.1248/yakushi.12-00278-1
|View full text |Cite
|
Sign up to set email alerts
|

The Antitumor Effects of a Plant Extract Mixture

Abstract: The authors declare no con‰ict of interest. a 福岡大学薬学部医薬品情報学教室(〒814 0180 福岡 市城南区七隈 8 19 1) , b 株式会社紀文食品国際事業室 (〒206 0812 東京都稲城市矢野口 86) , c サン自然薬研 究所(〒104 0061 東京都中央区銀座 3 12 6)  e-mail: ononob@fukuoka-u.ac.jp 本総説は,日本薬学会第 132 年会シンポジウム S28 で 発表したものを中心に記述したものである. Cancer is the most common cause of death in Japan. Fundamental and clinical studies on cancer were conducted from the viewpoint of Western medicine so far. However, a sustained complete remission has not been achieved yet. In order to alleviate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Although no evidence of tumor regression was documented in any of the 12 dogs treated, this study was not designed as an efficacy trial, and a potential role for Rv-PEM01 as a complementary or alternative therapy for cancer treatment, or a role in chemoprevention, remains to be explored. Dosages of Rv-PEM01 evaluated here are significantly less than what is needed to produce antiproliferative effects in vitro [11] [12] suggesting that further studies are warranted in dogs at significantly higher dosage levels.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Although no evidence of tumor regression was documented in any of the 12 dogs treated, this study was not designed as an efficacy trial, and a potential role for Rv-PEM01 as a complementary or alternative therapy for cancer treatment, or a role in chemoprevention, remains to be explored. Dosages of Rv-PEM01 evaluated here are significantly less than what is needed to produce antiproliferative effects in vitro [11] [12] suggesting that further studies are warranted in dogs at significantly higher dosage levels.…”
Section: Resultsmentioning
confidence: 91%
“…The branches and sap from R. verniciflua contain active compounds such as urushiol, fustin, querce tin, butein and sulfuretin; the antioxidant [15] [16], antitumorigenic [17] and cytotoxic [18] effects of these compounds have been reported. The antiproliferative activity of Rv-PEM01 has been demonstrated in human, mouse, and canine cell lines [11] [12]. Notably, D17, the one canine cell line that has been tested, is the most sensitive cell line tested to date [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antitumour effects of RvPEM01 have been evaluated in vitro, and the findings showed that Rv-PEM01 exhibited antiproliferative activities in human, mouse, and canine tumour cells. In particular, MOLT-3, KG-1, Colon-26, and D-17 cells were more sensitive to Rv-PEM01 than other cell lines [2,3]. We presumed that Rv-PEM01 induces apoptosis in tumour cells in vitro [3].…”
Section: Introductionmentioning
confidence: 89%
“…In particular, MOLT-3, KG-1, Colon-26, and D-17 cells were more sensitive to Rv-PEM01 than other cell lines [2,3]. We presumed that Rv-PEM01 induces apoptosis in tumour cells in vitro [3]. However, the underlying mechanism of the antiproliferative effects of RvPEM01 on tumour cells remains unknown.…”
Section: Introductionmentioning
confidence: 99%